Efficacy and safety of inhaled extrafine beclomethasone dipropionate in adults with asthma: a randomized, parallel-group, dose-ranging study (BEAM). (13th June 2022) - Montanaro, Anthony; Weinstein, Steven; Beaudot, Carolyn; Scott, Sue M.; Georges, George
Abstract: Introduction: This manuscript describes a Phase II, dose-ranging, randomized, double-blind, placebo- and active-controlled, parallel-group study conducted to identify the appropriate dose of beclomethasone dipropionate (BDP) to be used in a single-inhaler extrafine formulation triple combination of BDP, formoterol fumarate and glycopyrronium.Methods: Patients aged 18–75 years with poorly-controlled asthma, receiving low/medium-dose inhaled corticosteroid (ICS), and who had forced expiratory volume in the 1st second (FEV1 ) 50–85% predicted, were randomized to inhale BDP 50, 200 or 400 µg twice daily (BID; total daily doses of 100, 400 and 800 µg), placebo, or the active comparator QVAR® 160 µg BID, all via pressurized metered-dose inhalers for 8 weeks. The primary objective was to evaluate superiority of BDP over placebo for change from baseline in pre-dose morning FEV1 at Week 8. ClinicalTrials.gov: NCT03084718.Results: Of 610 patients randomized, 559 (91.6%) completed the study. For pre-dose morning FEV1 at Week 8, BDP 200 µg BID was superior to placebo, with a statistically significant difference of 113 ml (95% CI 18, 209); differences vs placebo for BDP 50 and 400 µg BID were not significant (44 [–52, 140] and 93 [–3, 188] ml, respectively). Secondary efficacy endpoint results supported the primary endpoint in identifying BDP 200 µg BID as the appropriate dose. Adverse events were experienced by 23.5, 25.0 and 30.6% patients with BDP 50, 200 and 400 µg BID, 34.7% with placebo, and 30.6% with the active comparator.Conclusion: In this dose-ranging study, BDP 200 µg BID offered the optimal balance of efficacy and safety in patients with asthma poorly controlled on low/medium-dose ICS. Supplemental data for this article is available online at at www.tandfonline.com/ijas .